CHARACTERISTICS OF THE FAMILY MODELS IN URBAN AND RURAL AREAS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
A large segment of the history of family functioning is dominated by the traditionalfamily model, which is initially associated with existence in rural areas and it has beencharacterized with authoritarianism, predictability, repeatability, and solidarity. However,with the processes of industrialization and urbanization, the family is facing new challengesand problems. Following such social changes, the need for a functional family reorganizationis inevitable. New urban living prosperity way of living created a model of a modern nuclearfamily with their own characteristic. The processes of globalization clearly affect the changesof the primary group, ie its functions on a global level. However, the question is whethertoday, taking into account all these changes and influences, different family models are stillobserved in urban and rural areas. This research is aimed to analyze the impact of urban andrural areas on the characteristics of family models. A quantitative survey of 30 families will beconducted, of which 15 from urban and 15 from rural areas. The analysis of the answers willbe used to determine the similarities and differences of family models that exist in differentenvironments.